PELUANG USAHA MELALUI AGRIBISNIS MINA PADI UNTUK MENINGKATKAN PENDAPATAN PETANI - Sularno, Sularno; Jauhari, Sodiq (Universitas Sebelas Maret, 2014)
Food is a commodity that is very strategic and always needed by the community. Therefore the food supply must be guaranteed to meet the needs of the community. The agricultural sector has a very important role in the national food supply. Dominant contribution of the agricultural sector particularly in strengthening food security. Respect it is necessary to find a solution to support the improvement of food security programs geared to meet the food needs of the community. To support the activities of the program has been carried out assessment of business opportunities through farming fish rice to increase farmers' income. In the implementation of this study by utilizing irrigated land area of 1 hectare for rice farming and business varieties Sidenuk of fish nila. Data type of the data collected primary and secondary data. To support the study used a SWOT (Strenght, Weakness, Oppotrtunity and Threath) analysis, while for the feasibility analysis used R/C ratio and B/C ratio. The study showed that agribusiness fish rice farming can provide an additional net profit of 7,165.250 million (35.29%), with the R/C ratio of 2.97 and B/C ratio of 1.97. Based on the assessment results, the agribusiness farming fish rice developed feasible.